Influence of phenotypic variation of Paenibacillus polymyxa E681 on growth promotion in cucumbers - Lee, Younmi; Kwon, Sungmoon; Balaraju, Kotnala; Jeon, Yongho (Frontiers in Microbiology, 2024)
The goal of the current study is to better understand how bacteria may adapt to survive under adverse environmental conditions by altering and improving their phenotypes. In this study, we report the consequences of phenotypic variation in Paenibacillus polymyxa E681 (E681), a plant growth-promoting rhizobacterium (PGPR), isolated from winter barley root that has a variety of advantageous effects on crop plants. In our study, two different types of bacterial cells in E681 were distinguished. We used the terms F-type for variations and B-type for the wild type. Under the circumstances of our experiment, the cucumber rhizosphere soil and the surface of the seeds produced phenotypic variance. On tryptic soy agar (TSA) plates, the B-type was converted into the F-type, but the reverse was not reversible. Intriguingly, the plant growth promotion test displayed that cucumber seedlings treated with F-type cells had characteristics resembling those of the untreated control. Whereas, growth promotion of cucumber seedlings treated with B-type depends on temperature conditions. In particular, an increased growth promotion was observed at a low temperature of 20°C. The phenotypic change in the B-type did not occur at 20°C for 6 days in the growth curve analysis of E681, but it did occur on the fourth and second days at 30°C and 37°C, respectively. Therefore, before using PGPR strains as a bacterial inoculant for sustainable agriculture, it is imperative to resolve phenotypic variance in these strains.